SiOC Phase Control and Carbon Nanoribbon Growth by Introducing Oxygen at Atom Level for Lithium‐Ion Batteries. Issue 12 (4th November 2022) - Wu, Pengfei; Zheng, Zhicheng; Shi, Benyang; Liu, Chao; Chen, Shaohong; Xu, Binbin; Liu, Anhua
Abstract: Poor intrinsic conductivity and the presence of irreversible lithiation phase affect the electrochemical performance of silicon oxycarbide anode materials. Even though it can be improved by increasing free carbon content or composition, scarification of reversible capacity and initial Coulombic efficiency (ICE) remain as challenge. Here, polycarbosilane (PCS) with alternating distribution of silicon and carbon atoms is employed as precursor of SiOC ceramics. Air oxidation cross‐linking is used to regulate the content of oxygen and carbon elements in PCS at atom level, so as to explore a solution to improve the intrinsic conductivity and reversible lithium phase content of SiOC ceramics. This strategy provides extremely excellent rate capability, areal/volumetric capacity, and ICE. This is also the first concept for feasible precursor structure design to control the SiOC glass phase and regulate the growth of C nanoribbon that can improve the intrinsic conductivity and reversible capacity of SiOC ceramic anode materials. Abstract : Air oxidation cross‐linked polycarbosilane with alternating distribution of Si and C atoms is employed as precursor of SiOC ceramics. By this strategy, intrinsic conductivity and reversible lithium phase content are optimized by O distribution and C nanoribbons, and extremely excellent rate capability, areal/volumetric capacity, initial Coulombic efficiency are achieved.